Effectiveness of Kepok Banana Peel Waste With Potassium Hydroxide Activation as Methylene Blue Dye Adsorbent - Sidabutar, Putri Rebecca; Kembaren, Agus (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
Banana peels are usually considered as waste and cause environmental pollution. However, banana peels can be used as an adsorbent material to reduce the impact of methylene blue dye use because they contain high lignocellulose. This study aims to determine the characterization, optimum mass and optimum time. The adsorbent was made using dried and carbonized banana peels at a temperature of 400°C for 2 hours. After the carbonization process, the adsorbent was activated using 5 M potassium hydroxide for 2.5 hours. Based on the results of the study, it showed an optimum mass of 0.121 grams and an optimum time of 90 minutes. The efficiency of methylene blue dye absorption on activated carbon was higher than that of banana peel carbon.